Ultra-broadband acoustic absorber based on periodic acoustic rigid-metaporous composite array - Dongguo Zhang; Fei Sun; Yichao Liu (Discover Applied Sciences)
Abstract To address the increasingly serious issue of noise pollution, we propose an ultra-broadband, wide-angle acoustic absorber based on a periodic acoustic rigid-metaporous composite array. Numerical simulation results verify its exceptional ultra-broadband acoustic absorption performance, achieving an average absorption coefficient of 90.9% across a frequency range from 500 to 4000 Hz and incident angles within ± 75 degrees. Compared to other acoustic absorbers of similar size, our design offers superior absorption performance, while maintaining a more compact structure than absorbers with comparable efficiency. This work will provide a new approach for ultra-broadband and wide-angle acoustic wave absorption, with significant potential for noise suppression.